Análisis de la cuenta propiedad, planta y equipo en el Gobierno Autónomo Descentralizado Municipal del cantón Vinces en el periodo 2022. - Bernita Villamar, Jhankel Benito (2023)
The case study focuses on the analysis of the Property, Plant and Equipment (PPE) account of the Municipal Decentralized Autonomous Government of the Vinces Canton during the period 2022. PPE assets are tangible and durable assets used to support the long-term production and delivery of services in a company. International Accounting Standard (IAS) 16 governs the accounting treatment of these assets. The problem raised is how the PPE account is being managed in the Municipal GAD of Vinces during the mentioned period, considering the importance of proper management of these assets to ensure efficiency in the provision of public services and the efficient use of public resources. The research will help to obtain the analysis of aspects such as the process of recognition and registration of PPE assets, examine the control procedures to ensure that the assets are in good condition and verify the methodology used to calculate the depreciation of the assets. Likewise, the research is framed in the subline of Audit and Control, and methods such as documentary and descriptive research are used, as well as observation and interview instruments.